MODERN TECHNOLOGIES OF DISTANCE LEARNING - KUCHAI, Oleksandr; DEMIANIUK, Antonina (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The article highlights the principles of formation and development of distance learning, which involves the physical separation of teachers and students during the educational process using various technologies to facilitate and simplify communication between teacher and student and between students. It is established that the successful implementation of distance learning is highly dependent on the orderly implementation and consistent application of a set of methods and processes that provide online access to educational materials on the basis of interactive interaction of participants in the educational process. The study of the development of distance learning in Ukraine allowed us to identify the following stages: in 2002 an experiment on distance learning was introduced; in 2003 the Program of development of the distance learning system for 20004–2006 was adopted; in 2004 the first Regulation on distance learning was developed; in 2013 a new Regulation on distance learning taking into account the development of modern technologies and the Concept for the development of distance education in Ukraine were approved. In accordance with these regulations, the definition of the term "distance learning" is formulated. It is determined that distance learning technologies are a set of methods, forms and means of interaction of participants in the educational process in the process of independent assimilation of a certain array of knowledge while exercising appropriate control over their assimilation. Information technologies of distance learning are systematized with their further separation into presentation forms of educational materials, methods of delivery of educational materials, types of interaction of participants of educational process. The structure of distance learning with the use of such online services as Google Classroom or Khan Academy is described; video conferencing platforms such as Zoom or Skype. The characteristic features and advantages of using the online platform Moodle are identified. The world practice of using modern distance learning technologies with the definition of dominant online platforms (Canvas, Blackboard, Brightspace and Moodle) and a high level of perception of distance learning has been studied. The advantages of using modern distance learning technologies and the prospects of further exploration in the context of the development of innovative technologies for informatization and intellectualization of society are outlined.